2009
DOI: 10.1016/j.febslet.2009.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analyses of the response of cyanobacteria to different stress conditions

Abstract: a b s t r a c tCyanobacteria are significant contributors to global photosynthetic productivity, thus making it relevant to study how the different environmental stresses can alter their physiological activities. Here, we review the current research work on the response of cyanobacteria to different kinds of stress, mainly focusing on their response to metal stress as studied by using the modern proteomic tools. We also report a proteomic analysis of plastocyanin and cytochrome c 6 deletion mutants of the cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 54 publications
0
28
1
Order By: Relevance
“…Crucially, this "hot-bunking" reduces overall demand for iron, and enables Crocosphaera to do well in oligotrophic environments. Further, recent illustrative examples in which proteomes have been studied in the context of metal ions include studies on metal stress in cyanobacteria [31], in a brown alga [32], and metal-mediated protein dynamics in plants [33]. In addition, recent quantitative "pure" proteomics approaches have also uncovered links with metal ions, for example as shown in Ref.…”
Section: Metalloproteomicsmentioning
confidence: 97%
“…Crucially, this "hot-bunking" reduces overall demand for iron, and enables Crocosphaera to do well in oligotrophic environments. Further, recent illustrative examples in which proteomes have been studied in the context of metal ions include studies on metal stress in cyanobacteria [31], in a brown alga [32], and metal-mediated protein dynamics in plants [33]. In addition, recent quantitative "pure" proteomics approaches have also uncovered links with metal ions, for example as shown in Ref.…”
Section: Metalloproteomicsmentioning
confidence: 97%
“…Past studies on Synechocystis have revealed that elements such as copper and iron can alter the expression of primary metabolism proteins as well as the expression of general stress proteins such as proteases, chaperones, and sigma factors (54). Recent studies on Synechocystis and Anabaena have demonstrated that iron limitation leads to the expression of the iron stress-induced protein (IsiA) and flavodoxin (IsiB), which act to protect and support the cyanobacterial photosystem (23,55).…”
Section: Discussionmentioning
confidence: 99%
“…The GroEL proteins are commonly induced by almost all stresses, including heat stress (Apte et al, 1998). Proteomic analyses of Synechocystis PCC6803 exposed to heat, salt or metal stresses similarly indicate the presence of several common proteins, including chaperones and sigma (Sig) factors (Castielli et al, 2009). Protein denaturation occurs in response to almost all abiotic stresses, resulting in accumulation of denatured proteins in the cytosol.…”
Section: The Hsr In Cyanobacteriamentioning
confidence: 99%